Mesenchymal chondrosarcoma of bone and soft tissue: a systematic review of 107 patients in the past 20 years. - Jie Xu; Dasen Li; Lu Xie; Shun Tang; Wei Guo (PLoS ONE)
Background Mesenchymal chondrosarcoma(MCS) is a rare high-grade variant of chondrosarcoma. Consensus has not been reached on its optimal management. Resection with wide margins is usually recommended, but the effect of margins has been demonstrated by little positive evidence. Moreover, the effectiveness of adjuvant chemo- and/or radiotherapy remains controversial. Objectives To describe the clinical characteristics and outcomes of MCS of bone and soft tissue, to assess the efficacies of surgery, chemotherapy and radiation, and finally to deliver a more appropriate therapy. Materials and methods We reviewed EMBASE-, MEDLINE-, Cochrane-, Ovid- and PubMed-based to find out all cases of MCS of bone and soft tissue described between April 1994 and April 2014. Description of treatment and regular follow-up was required for each study. Language was restricted to English and Chinese. Issues of age, gender, location, metastasis, and treatment were all evaluated for each case. Kaplan-Meier Method and Cox Proportional Hazard Regression Model were used in the survival analysis. Results From the 630 identified publications, 18 meeting the inclusion criteria were selected, involving a total of 107 patients. Based on these data, the 5-, 10-and 20-year overall survival are 55.0%, 43.5% and 15.7% respectively. The 5-, 10-, 20- year event-free survival rates are 45.0%, 27.2% and 8.1%, respectively. Treatment without surgery is associated with poorer overall survival and event-free survival. Negative surgical margins could significantly bring down the local-recurrence rate and are associated with a higher event-free survival rate. Chemotherapy regime based on anthracyclines does not benefit the overall survival. The addition of radiation therapy is not significantly associated with the overall or event-free survival. However, we recommend radiation as the salvage therapy for patients with positive margin so as to achieve better local control. Conclusions This review shows that surgery is essential in the management of MCS of bone and soft tissue. Appropriate adjuvant therapy may reduce local recurrence, but cannot benefit the overall survival.